Imbalanced effector and regulatory cytokine responses may underlie mycobacterial immune restoration disease - Lim, A.; D'Orsogna, L.; Price, Patricia; French, M. (2008)
Background: Immune restoration disease (IRD) is an adverse consequence of antiretroviral therapy, where the restored pathogen-specific response causes immunopathology. Mycobacteria are the pathogens that most frequently provoke IRD and mycobacterial IRD is a common cause of morbidity in HIV-infected patients co-infected with mycobacteria. We hypothesised that the excessive effector immune response in mycobacterial IRD reflects impaired regulation by IL-10. Results: We studied two patients who experienced mycobacterial IRD during ART. One patient developed a second episode of IRD with distinct clinical characteristics. Findings were compared with patients 'at risk' of developing IRD who had uneventful immune recovery. Peripheral blood mononuclear cells (PBMC) from all subjects were stimulated with mycobacterial antigens in the form of purified protein derivative (PPD). Supernatants were assayed for IFN? and IL-10. In response to PPD, PBMC from IRD patients generated IFN? during the first IRD episode, whilst cells from non-IRD controls produced more IL-10. Conclusion: We present preliminary data from two HIV-infected patients showing an imbalance between IFN? and IL-10 responses to mycobacterial antigens during mycobacterial IRD. Our findings suggest that imbalanced effector and regulatory cytokine responses should be investigated as a cause of IRD. © 2008 Lim et al; licensee BioMed Central Ltd.